Informing the development of a decision aid: Expectations and wishes from service users and psychiatrists towards a decision aid for antipsychotics in the inpatient setting - Katharina Müller; Florian Schuster; Silvia Krumm; Stefan Leucht; Spyridon Siafis; Stephan Heres; Peter Brieger; Johannes Hamann (Wiley, 2023)
Abstract Objectives Decision aids (DAs) are promising tools to foster evidence‐based shared decision‐making between practitioners and service users. Nevertheless, it is still obscure how an evidence‐based DA for people with severe mental illness, especially psychosis, should look in an inpatient treatment setting to be useful and feasible. Therefore, we conducted focus groups with psychiatrists and service users to collect and assess their expectations and wishes regarding an evidence‐based DA. From these findings, we derived immediate recommendations for the future development of DAs. Methods We held two group interviews with service users (n = 8) and three group interviews with psychiatrists (n = 10). We used an open, large‐scale topic guide. First, we presented data from a current meta‐analysis on antipsychotics to the interviewees and, in a second step, asked for their expectations and wishes towards a DA that integrates these data. Results Our thematic analysis revealed six key themes addressed by the respondents: (1) general considerations on the importance and usefulness of such a DA, (2) critical comments on psychiatry and psychopharmacotherapy, (3) communicative prerequisites for the use of a DA, (4) form and content of the DA, (5) data input, data processing and output as well as (6) application of the DA and possible obstacles. Conclusions Participants identified several important features for the development of DAs for selecting antipsychotics in inpatient psychiatric treatment. The digital format was met with the greatest approval. Especially the adaptability to different needs, users and psychopathologies and the possibility to outsource information dissemination via app seemed to be a decisive convincing argument. Further research is required to test specific features of DAs to be developed in clinical settings.